Investigation of Mechanical Properties of E-Waste Polymer Blend - Sharma, Sanjay; Santhosh, G; G Pradeepa, K (International Journal of Engineering and Technology, 2018)
E-waste collection has turned into a noteworthy worry for the greater part of the natural issues. The E-waste aggregation turns into a quick natural issue which can build up the human wellbeing risks, for example aggravation and oxidative pressure forerunner to cardiovascular illnesses, malignancy, skin ailments, and DNA harm and so forth. Supplanting the E-waste into the valuable items is the major testing process. In this study WEEE plastics and pure polypropylene is blended in different composition and investigation of its tensile flexural and impact properties is done in order to improve mechanical properties by optimizing the right composition which have larger volume than that of E-waste.Â